Hairstreak butterflies (Lepidoptera, Lycaenidae) and evolution of their male secondary sexual organs. (25th September 2018) - Pereira Martins, Ananda Regina; Duarte, Marcelo; Robbins, Robert K.
Abstract: Hairstreak butterflies in the Atlides Section of the Eumaeini are biologically notable for a diverse array of male secondary sexual organs. A "species recognition" hypothesis postulates that females use these organs to choose between conspecific and non‐conspecific males, thereby promoting reproductive isolation. Alternately, a "sexual selection" hypothesis posits that females use these organs to choose among conspecific males. These hypotheses need not be mutually exclusive but make different predictions about the evolutionary gain and loss of male secondary sexual organs. We analysed most of the Atlides Section (Theclinae, Eumaeini) phylogenetically. Sister lineages were sympatric at 22 of 37 nodes. Nine evolutionary gains occurred in lineages that were sympatric with their phylogenetic sister, and one occurred in a lineage that was allopatric/parapatric with its sister. By contrast, seven of ten evolutionary losses occurred in lineages that were allopatric/parapatric with their sisters. These results are significantly different from those predicted by a sexual selection hypothesis. We conclude that male secondary sexual organs in the Atlides Section function primarily for species recognition and thereby promote sympatric diversification.